2012
DOI: 10.1007/s10706-011-9488-8
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Geogrid Encased Stone Columns

Abstract: Stone columns in soft soil improve bearing capacity because they are stiffer than the material which they replace, and compacted stone columns produce shearing resistances which provide vertical support for overlying structures or embankments. Also stone columns accelerate the consolidation in the native surrounding soil and improve the load settlement characteristics of foundation. In this paper, the finite element method is utilized as a tool for carrying out analyses of stone column-soil systems under diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 2 publications
1
15
0
Order By: Relevance
“…However, little research focused on treatmentfor collapsible soil in which water inclusion was not ideally represented.On other hand, there are several local publications focused on encased stone columns to improve soft soils. Recent example on that by (Fattah &Majeed 2012) in which finite element analysis had been employed to study a geogrid encased stone columns that are assumed to be supported by a soft clay layer. (Buringh 1960) outlined the main features of soil conditions in Iraq according to the geomorphological regions: the Mountains and foothill region, the Mesopotamian plain, and the Deserts (see Fig.…”
Section: Previous Researches On Stone Columns In Iraqmentioning
confidence: 99%
“…However, little research focused on treatmentfor collapsible soil in which water inclusion was not ideally represented.On other hand, there are several local publications focused on encased stone columns to improve soft soils. Recent example on that by (Fattah &Majeed 2012) in which finite element analysis had been employed to study a geogrid encased stone columns that are assumed to be supported by a soft clay layer. (Buringh 1960) outlined the main features of soil conditions in Iraq according to the geomorphological regions: the Mountains and foothill region, the Mesopotamian plain, and the Deserts (see Fig.…”
Section: Previous Researches On Stone Columns In Iraqmentioning
confidence: 99%
“…A trial was conducted by Fattah and Majeed (2012) to improve the behavior of a stone column by encasing the stone column with a geogrid as reinforcement material. A parametric study was carried out to investigate the behavior of standard and encased floating stone columns in different conditions.…”
Section: Geogrid Encased Stone or Sand Columnsmentioning
confidence: 99%
“…When the load was applied to the tank wall, the load/settlement behavior was linear and the failure did not take place. Fattah & Majeed (2012b) studied the geogrid-encased floating stone columns and found that the maximum lateral displacement occurred at an effective encasement length ratio (length of geogrid encasement along the stone column/total stone column length) of 0.6. Gniel & Bouazza (2009) carried out experiments on geogrid-encased stone columns and found that maximum bulging occurred at a depth of 2D.…”
Section: Introductionmentioning
confidence: 99%
“…Damoerin et al (2015) carried out a series of tests to increase the shear strength of the soil by improving the cement column and found that this increased the shear strength of the soil. Fattah and Majeed (2009) studied the behavior of encased floating stone columns and found that the bearing improvement ratio increased by increasing the area replacement ratio for both ordinary and encased stone columns. Fattah et al (2010) carried out tests on stone columns by varying the SCR and found that the stiffness was increased with an increase in stiffness of the treated soil.…”
Section: Introductionmentioning
confidence: 99%